The end of the 'iron rice-bowl': whither Chinese human resource management? - Ding, Daniel Z.; Goodall, Keith; Warner, Malcolm (International journal of human resource management, 2000)
This study examines the degree to which enterprise reforms in the PRC have affected human resource management practices over the 1990s. A comparison is made between state-owned enterprises and joint venture firms, involving a national sample of sixty-two companies ranging from those in the North to those in the South. Our main findings show how organizational inertia has obstructed the change of the mind-sets associated with the 'iron rice-bowl' that characterized Chinese state-owned enterprises (SOEs) before economic reform. The main conclusions of the research point to ownership, location and size of the firm as the main factors affecting the evolution of HRM in Chinese enterprises.